2019
DOI: 10.1016/j.omtm.2019.10.005
|View full text |Cite
|
Sign up to set email alerts
|

rAAVrh74.MCK.GALGT2 Demonstrates Safety and Widespread Muscle Glycosylation after Intravenous Delivery in C57BL/6J Mice

Abstract: rAAVrh74.MCK.GALGT2 is a surrogate gene therapy that inhibits muscular dystrophy in multiple animal models. Here, we report on a dose-response study of functional muscle GALGT2 expression as well as toxicity and biodistribution studies after systemic intravenous (i.v.) delivery of rAAVrh74.MCK.GALGT2. A dose of 4.3 × 1014vg/kg (measured with linear DNA standard) resulted in GALGT2-induced glycosylation in the majority of skeletal myofibers throughout the body and in almost all cardiomyocytes, while several low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 47 publications
5
12
0
Order By: Relevance
“…Non-muscle organs assessed included the brain (cerebellum and frontal cortex), spinal cord, lung, pancreas, liver, spleen, adrenal gland, kidney, and gonads (ovary or testicle) ( Fig 1C ). As expected, based on previous work in mice and rhesus macaques [ 68 , 69 ], the greatest transduction for rAAVrh74 was in the liver and spleen (12 and 8 vg/nucleus, respectively), while the lowest level of transduction was in the brain (both cerebellum and frontal cortex <0.1vg/nucleus). Unexpectedly, pancreas also showed a very low level of transduction (also <0.1vg/nucleus), a finding not seen previously in mice or in macaques [ 68 , 69 ].…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Non-muscle organs assessed included the brain (cerebellum and frontal cortex), spinal cord, lung, pancreas, liver, spleen, adrenal gland, kidney, and gonads (ovary or testicle) ( Fig 1C ). As expected, based on previous work in mice and rhesus macaques [ 68 , 69 ], the greatest transduction for rAAVrh74 was in the liver and spleen (12 and 8 vg/nucleus, respectively), while the lowest level of transduction was in the brain (both cerebellum and frontal cortex <0.1vg/nucleus). Unexpectedly, pancreas also showed a very low level of transduction (also <0.1vg/nucleus), a finding not seen previously in mice or in macaques [ 68 , 69 ].…”
Section: Resultssupporting
confidence: 87%
“…As expected, based on previous work in mice and rhesus macaques [ 68 , 69 ], the greatest transduction for rAAVrh74 was in the liver and spleen (12 and 8 vg/nucleus, respectively), while the lowest level of transduction was in the brain (both cerebellum and frontal cortex <0.1vg/nucleus). Unexpectedly, pancreas also showed a very low level of transduction (also <0.1vg/nucleus), a finding not seen previously in mice or in macaques [ 68 , 69 ]. Transduction of the spinal cord was significantly higher than brain, again as before [ 68 , 69 ].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, previous mouse studies have shown that similar doses of vector, but with different DNA cargo, were well tolerated up to 5 × 10 14 vg/kg, without noticeable cardiotoxicity at long term. 47 , 48 , 49 , 50 , 51 In the current study, we did not investigate the potential involvement of the innate or adaptive immune response against the vector, transgene, and/or transduced cells. 35 , 36 , 52 , 53 It is likely that the treated mice developed a humoral response against the capsid, including neutralizing antibodies, as shown previously in many mouse gene therapy studies.…”
Section: Discussionmentioning
confidence: 99%
“… 35 , 36 , 52 , 53 It is likely that the treated mice developed a humoral response against the capsid, including neutralizing antibodies, as shown previously in many mouse gene therapy studies. 50 , 51 However, the emergence of antibody against the capsid has not been shown to preclude the long-term expression of transgene or to drive cardiac inflammation but only the re-administration of the same vector. 54 Here, we did not explore the potential presence of antibodies against the transgene and, more importantly, the development of a potential cytotoxic cell response targeting the transduced cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%